Kinetics of adsorption of Cu(II) and Cd(II) from aqueous solution on rice husk and modified rice husk - Soon-an, Ong; Chye-Eng, Seng; Poh-Eng, Lim (University of Vigo, 2009)
Fulltext of this article is also available at http://ejeafche.uvigo.es/